PENGARUH GRADASI AGREGAT TERHADAP KARAKTERISTIK BETON SEGAR - pertiwi, Nurlita (FORUM BANGUNAN, 2014)
The aim of this research isÂ  to know the effect of gradation natural aggregate to the characteristic of fresh concrete. Gradation of aggregate are found from composition of size granular fine and coarse aggregate. The method of research is an experimental method. Sample were made from four kinds of fine aggregate (zone 1,2,3, dan 4) and three kinds of coarse aggregate with the same composition. The result of research are good slump value made from zone 1 (very rough), zone 2 (rough), and zone 3 (fine). The fine aggregate with fines granular (zone 4) give eligible slump if mixed with coarse aggregate size of 40 mm. Required the appropriate bleeding acquired in the use of fine aggregate zone 1, zone 2, zone 3 and zone 4. Maximum grain size of coarse aggregate has no effect on the bleeding produced. The appropriate density factor required is obtained on the use of fine aggregate zone 1 and zone 2. Maximum grain size of coarse aggregate has no effect on the density of the resulting.